Kointegrasi Indeks Saham Sektor Agro Dan Marine Sebagai Sumber Referensi Diversifikasi Internasional Bagi Investor Indonesia - Rahmadani, Ika; Damrus, Damrus; Irmalis, Amsal (Universitas Teuku Umar, 2023)
The research aims to evaluate the long-term relationship or cointegration between the Indonesian Stock Exchange and stock exchanges in the world. The novelty of the results of this research is that the results of cointegration will be presented in tabular form so that this table will later become a reference source for local investors in forming portfolios and utilizing diversification strategies to gain profits. Weekly data or weekly Index Prices is the main data from the agro and marine industries sector stock index of the Indonesian Stock Exchange (IDX) and other country stock exchanges in the world from January 2010 to December 2020 (11 years). The next step is that the data will be used in testing using the Johansen Test method. The results of this research show that only two stock price indices have cointegration with the Indonesian agro and marine stock indices. So the agro and marine sectors generally do not have integration and investors still have the opportunity to carry out diversification strategies.